Harnessing the Potential of Long Non-coding RNAs to Manage Metabolic Diseases - Bandesh, Khushdeep; Masih, Daisy; Bhattacharyya, Nirjhar; Bharadwaj, Dwaipayan (Current Pharmaceutical Design, 2021)
Long non-coding RNAs (lncRNAs) are functionally versatile molecules that regulate gene expression at all levels of biological organization. RNA modulation, at the moment, has emerged as a powerful therapeutic technique to treat human diseases. Lately, lncRNAs have been acknowledged as key players in human metabolism and, indeed, implicated in the etiology of many common diseases other than cancers, where they can perhaps serve as reliable markers to determine disease status or assess outcomes of an intervention. Here, in this review, we cite examples of such lncRNAs, discuss their mechanistic role in human diseases and their genetic association, quote potential biomarkers found in human blood, summarize the methods for therapeutic targeting lncRNAs and examine the progress of lncRNA based drugs in clinical trials. Thus, we propose that lncRNAs serve as both a biomarker and an effective therapeutic target with promising clinical utility to manage human metabolic diseases.
Keywords: lncRNAs